A Study on the Algorithms for Equilibrium Problems on Hadamard Manifolds - Rohtash (International Journal of Mathematics And its Applications, 2017)
The theory of equilibrium problems provides a unified, natural and general framework to study a wide class of problems, which arise in finance, economics, network analysis, transportation and optimization. This theory has applications across all disciplines of pure and applied sciences. Equilibrium problems include variational inequalities and related problems. The aim of this paper is to provide a survey on the algorithms for equilibrium problems that have been studied by many authors on Hadamard manifolds. This paper should be a useful reference for further research in the field of equilibrium problems and Hadamard manifolds.